Bacteraemia due to recurrent reinfection with Staphylococcus epidermidis associated with defective opsonisation and procidin function in serum. Issue 5 (May 1993) - Baker, L R; Brown, A L; Stephenson, J R; Tabaqchali, S; Zatouroff, M; Parkin, J M; Pinching, A J
Abstract : AIMS--To differentiate between reinfection and relapsing infection with Staphylococcus epidermidis in a middle-aged woman with defective opsonisation and procidin function in serum. METHODS--Microbiological typing was done by biotyping, phage typing, and polyacrylamide gel electrophoresis of radiolabelled bacterial proteins (radioPAGE method). Polymorphonuclear cell function was assessed in vitro by phagocytosis and killing of Candida albicans; measurement of neutrophil random locomotion and chemotaxis; reduction of nitroblue tetrazolium after stimulation by opsonised Candida and a radiometric saccharomyces opsonisation assay. The effect of plasma infusions on opsonic activity was assessed by chemiluminescence using control polymorphonuclear leucocytes with a laboratory strain of S epidermidis opsonised with either patient or control serum. RESULTS--Recurrent reinfection with different strains of Staphylococcus epidermidis rather than relapsing infection was confirmed as having occurred by typing bacterial strains. The RadioPAGE method detected all the S epidermidis strains involved in this patient's illness. The patient's serum was shown to be defective in both opsonin and procidin function. The defects were correctable in vitro by the addition of normal serum. Clinical recovery occurred after repeated infusions of normal fresh frozen plasma and prolonged antibacterial treatment; antibacterial treatment alone was insufficient. CONCLUSIONS--The radioPAGE method is useful in distinguishing recurrent reinfection with S epidermidis from relapsing infection with this organism. Elucidation of the nature of, and underlying predisposition to, infection in the patient studied allowed a rational treatment plan of plasma infusion combined with antibacterial treatment to be devised which ultimately proved successful.